Kinetics and Typical Drying Rate Curve of Cucumber (Cucumis sativus L.) Slices - Olegario, Marín-Machuca; Eduardo, Candela-Díaz, José; Germán, Jáuregui-del Águila, Luis; Walter, Zambrano-Cabanillas, Abel; Enrique, Chinchay-Barragán, Carlos; Adolfo, Pérez-Ton, Luis; Rafael, Amaranto-Cortez, Carlos (Journal of Cultural Analysis and Social Change, 2025)
Using the experimental data obtained from the drying process of cucumber (Cucumis sativus L.) slices, the drying kinetics and the Typical Drying Rate Curve (TDRC) were developed, as presented in Table 1. This table includes: time and moisture increments; accumulated moisture and their respective units; the ratio between moisture variation and drying time; specific drying rate values; estimated and average moisture content; and the drying rate during the pre-critical period. Under stable drying operating conditions, the equipment was loaded with 1070 g of cucumber slice samples to obtain the experimental drying data, keeping constant the thickness, moisture, and hot-air temperature. The falling-rate period and drying rate depended on the internal moisture conditions and the water transport properties. From the drying kinetics, the following values were obtained: initial moisture content, critical moisture content, monomolecular layer moisture content, and equilibrium moisture content, corresponding to 3.40, 2.00, 1.95, and 0.38 grams of water per 100 grams of dry solid, respectively. The drying rate during the pre-critical period was 5.95 kg.h-1.m-2.